Factors Affecting the Neonatal Outcome with Anorectal Malformation in Underdeveloped Countries - Muhammad Nadeem Khan, Saqib Ismail, Syed Zakir Hussain Shah, Sajid Razzaq, Gohar Latif, Muzaffar Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: With optimal perioperative and postoperative care, the survival and outcomes of new-born with anorectal malformations (ARM) have improved significantly in developed countries, but sepsis, low birth weight, late presentation, and intense new-born care is still lacking in developing countries influencing the outcome. This analysis was conducted to assess aspects for poor outcomes (mortality) in new-born with anorectal malformations. Study Design: A prospective analytical study. Place and duration: In the Department of Paediatric Surgery at Divisional Headquarters Teaching Hospital Mirpur for six months duration from January 2021 to June 2021. Methods: 48 total consecutive neonates with anorectal malformations (ARMs) admitted to the Paediatric Surgery department were included. The studied variables comprised age at admission, birth weight, sex, type of malformation, sepsis at admission, type of surgery performed, postoperative issues, and their association with the results. Statistical analysis was executed with SPSS 21.0. Results: 48 neonates with ARM were enrolled in the study. 60.4% (29) of the research population are male neonates and 39.6% (19) are female neonates. 2.3 ± 0.7 days was the mean age at admission (minimum age was 1 day and the maximum 4 days) and 2.8 ± 0.9 kg was the mean body weight at birth (minimum weight was 1.7 kg, and the maximum weight was 4.5 kg). The communal reason of mortality in patients postoperative was sepsis (50%). There was a statistically significant correlation amid sepsis and low birth weight (p = <0.01) on admission (p = 0.002) with mortality. Comparing the result with age at the time of presentation (p = 0.19) and complications postoperatively (p = 0.18), no statistically significant correlation was found. Conclusions: Lack of trained midwives / LHV, Lack of resources, late admission, intensive care sepsis, and ultimately mortality are contributing factors in developing countries. Good prenatal care, awareness of midwives / community nurses to refer these patients on time, and adequate intensive care can improve the outcomes of ARM surgery.